Perception of the Organizational Climate and Safety Culture in the Surgery Service of a Level III-1 Emergency Hospital: Percepción del clima organizacional y cultura de seguridad en el servicio de cirugía de un hospital de emergencias nivel III-1 - Vega Vega, Robert Ricardo (2024)
To determine the correlation between the perception of organizational climate and the safety culture in the surgery department of the José Casimiro Ulloa Emergency Hospital (HEJCU), a descriptive and correlational study was conducted with 100 healthcare professionals, using the ECO-S and MOSPS questionnaires, respectively. The correlation was analyzed using Spearman's correlation coefficient, with p<0.05 considered statistically significant. Of the total, 57% were men and 43% women; 62% were physicians and 38% nurses. The organizational climate was adequate (43%), at risk (40%), and inadequate (17%); the safety culture was high (14%), medium (82%), and low (4%). A significant positive correlation was found between safety culture and organizational climate (rho=0.501), organizational behavior (rho=0.477), organizational structure (rho=0.494), and management style (rho=0.474) (p<0.001). In conclusion, there is a positive correlation between organizational climate and safety culture in the surgery department of HEJCU.